ANALYSIS AS A BASIS FOR TAKING MANAGEMENT DECISION - I. I. Chvankova (Литьë и металлургия)
The connecting-link between accounting and taking of management decisions is determined in the article. The system approach to analysis of the enterprise activity is described.